The Hunger Games - Collins, Suzanne (New York Scholastic Press, 2008)
In a future North America, where the rulers of Panem maintain control through an annual televised survival competition pitting young people from each of the twelve districts against one another, sixteen-year-old Katniss's skills are put to the test when she voluntarily takes her younger sister's place.
Keywords: Survival -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction